2015
DOI: 10.1353/hpu.2015.0005
|View full text |Cite
|
Sign up to set email alerts
|

Religiosity, Spirituality, and HIV Risk Behaviors among African American Women from Four Rural Counties in the Southeastern U.S.

Abstract: In a cross- sectional survey of 1,013 African American women from rural Alabama and North Carolina, we examined the relationship of (1) organizational religiosity (i.e., religious service attendance), (2) non- organizational religiosity (e.g., reading religious materials), and (3) spirituality with these outcomes: women’s reports of their sexual behaviors and perceptions of their partners’ risk characteristics. Women with high non-organizational religiosity, compared with low, had fewer sex partners in the pas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 38 publications
1
8
1
Order By: Relevance
“…This is worth exploring in a larger sample to determine whether African American women may incorporate religiousness in their healing more than White women. This complements research which indicates that African American women with HIV value religion in the context of healing 1,912. However, this difference was not significant for the IWSR.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…This is worth exploring in a larger sample to determine whether African American women may incorporate religiousness in their healing more than White women. This complements research which indicates that African American women with HIV value religion in the context of healing 1,912. However, this difference was not significant for the IWSR.…”
Section: Discussionsupporting
confidence: 75%
“…Spirituality and religiosity are associated with better physical and emotional health in studies of cancer patients. 7 , 8 In chronic illnesses such as human immunodeficiency virus (HIV), spiritual adjustment has been shown to improve health-related quality of life, 9 , 10 immune status, 11 risk behavior, 12 and sleep quality. 13 The increase in research examining the benefits of spirituality on disease progression and well-being has led to the development of several instruments to capture the aspects of spirituality and religiousness.…”
Section: Introductionmentioning
confidence: 99%
“…The other study by Ludema et al, 26 proved that participation in religious activities, such as reading and learning holy book and the faith to God was a strong barrier for sexual behaviors. 26 Furthermore, this study also reported that women having a high level of religiosity and spirituality tended to look for partners whose equal qualities to them, in which their partner had a low risk factor of getting HIV as well.…”
Section: Discussionmentioning
confidence: 92%
“…Our addition to this model is a series of variables on communication among networks of family and friends. In keeping with data on the importance of communication in health decisions (42,43), we propose that communication among family and friends, including the content and frequency of breast cancerrelated communication, influences individuals' thoughts and feelings about breast cancer risk and ultimately, their prevention behaviors. This influence may be positive (i.e., supporting screening) or negative.…”
Section: Intervention Behavioral Theorymentioning
confidence: 97%